A case of ocular thelaziasis in a 2.5 years old Holstein heifer (Veterinary Science Development, 2014)
A 2.5-years-old, Holstein lactating dairy cow was presented to the Veterinary Health Center with severe conjunctivitis and exuberant granulation tissue formation of the left eye. Upon close examination of the eye, a 2-cm long slender-shaped nematode was found in the conjunctival sac. The nematode was examined by a veterinary parasitologist and determined to be Thelazia species. The exuberant granulation tissue was surgically removed and a total of 0.5 mL of 1% levamisole was injected subconjunctivally. Levamesole was also injected subcutaneously at a dose of 10 mg/kg of body weight and repeated after 15 days. The cow made a complete recovery within 25 days following treatment. This is the first case report of ocular thelaziasis in dairy cattle in Jordan.